Evaluation of Neutrophil to Lymphocyte Ratio and Platelet to Lymphocyte Ratio in Covid-19 Patients Treated with Tocilizumab Due to Cytokine Storm - Serkan Yavuz; Cengiz Burnik; Mehmet Mermer; Faysal Duksal (Genel Tıp Dergisi)
Background/Aims: There is a significant increase in proinflammatory cytokine levels in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) patients entering cytokine storm. Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR), also increase in inflammatory diseases. The aim was to evaluate the NLR and PLR of coronavirus disease 2019 (COVID-19) patients receiving tocilizumab (TCZ) due to cytokine storm. Materials and Methods: In this retrospective, cross-sectional study conducted in between March and December 2020, adult patients with laboratory-confirmed COVID-19 were analyzed Results; The mean age of 519 patients included in the study was 61.6 ± 17.0 years, with male predominance (64.7%). 70.7% of patients had at least one type of comorbidity and the most common comorbid conditions were chronic obstructive pulmonary disease (45.9%) and asthma (28.7%). 399 patients who were given TCZ (group 1) and 120 patients who were not given TCZ (group 2) were evaluated. Compared with group 2, group 1 had more male predominance and they were older (p<0.001). The mortality rate, which was found to be 48.6% in group 1, was approximately twice as high in the intensive care unit (ICU). NLR and PLR were significantly higher and lymphopenia was more prominent in group 1, especially in ICU patients than group 2 (p<0.001). Conclusion: High NLR, PLR and lymphopenia was more common in critically ill Covid-19 patients. Therefore, they may be used as a marker to predict poor prognosis. It can be suggested to treat these patients more aggressively in the initial period.